Need Fulfillment and Resilience Mediate the Relationship between Mindfulness and Coping in Medical Students. Issue 1 (20th January 2022) - Neufeld, Adam; Malin, Greg
Abstract: Theory: Medical programs have turned to mindfulness-based initiatives to help reduce student distress and promote healthy coping within the learning environment. However, little attention has been paid to how fulfillment of medical students' basic psychological needs (autonomy, competence, and relatedness) impacts their capacity to be mindful and cope with stress. Self-Determination Theory (SDT) posits that mindfulness facilitates adaptive coping and wellness, in large part because of need fulfillment. Hypotheses: Using SDT as a lens, it is hypothesized that medical students' resilience and, to a greater extent, need fulfillment in medical school, will mediate the relationship between their mindfulness and coping reactions to stress. Method: One-hundred-ninety-seven medical students from the University of Saskatchewan were recruited to participate in this study: 71 first year, 58 second year, and 36 third and fourth year, each. Students completed an anonymous survey, measuring need fulfillment in medical school, mindfulness, resilience, and frequent use of various adaptive and maladaptive coping strategies. We assessed the extent that need fulfillment and resilience mediated the relationship between mindfulness and coping styles. Results: Need satisfaction and resilience fully mediated the relationship between mindfulness and adaptive coping. Conversely, need frustration and resilience partially mediated the relationship between mindfulness and maladaptive coping. Need fulfillment was a stronger mediator than resilience in both coping models. Conclusions: Findings suggest that increased supports for medical students' resilience and basic psychological needs may promote their mindfulness, and in turn, their ability to respond more adaptively and less maladaptively to stressors they face in medical school.